Multi‐Stage Phase‐Segregation of Mixed Halide Perovskites under Illumination: A Quantitative Comparison of Experimental Observations and Thermodynamic Models. (23rd November 2022) - Suchan, Klara; Just, Justus; Beblo, Pascal; Rehermann, Carolin; Merdasa, Aboma; Mainz, Roland; Scheblykin, Ivan G.; Unger, Eva
Abstract: Photo‐ and charge‐carrier‐induced ion migration is a major challenge when utilizing metal halide perovskite semiconductors for optoelectronic applications. For mixed iodide/bromide perovskites, the compositional instability due to light‐ or electrical bias induced phase‐segregation restricts the exploitation of the entire bandgap range. Previous experimental and theoretical work suggests that excited states or charge carriers trigger the process, but the exact mechanism is still under debate. To identify the mechanism and cause of light‐induced phase‐segregation phenomena, the full compositional range of methylammonium lead bromide/iodide samples are investigated, MAPb(Br x I1‐ x )3  with x = 0…1, by simultaneous in situ X‐ray diffraction (XRD) and photoluminescence (PL) spectroscopy during illumination. The quantitative comparison of composition‐dependent in situ XRD and PL shows that at excitation densities of 1 sun, only the initial stage of photo‐segregation is rationalized with the previously established thermodynamic models. However, a progression of the phase segregation is observed that is rationalized by considering long‐lived accumulative photo‐induced material alterations. It is suggested that (additional) photo‐induced defects, possibly halide vacancies and interstitials, need to be considered to fully rationalize light‐induced phase segregation and anticipate the findings to provide crucial insight for the development of more sophisticated models. Abstract : Photo‐ and charge‐carrier induced ion migration is a major challenge when utilizing metal halide perovskite semiconductors. It is uniquely apparent during the light‐induced phase‐segregation of mixed iodide/bromide perovskites. Here, its mechanism and cause is investigated by simultaneous in situ X‐ray diffraction and photoluminescence spectroscopy during illumination for the full compositional range of MAPb(Brx I1‐x )3  with x  =  0…1.